Aquaporin-4-autoimmunity in patients with systemic lupus erythematosus: a predominantly population-based study - Asgari, Nasrin; Jarius, Sven (Multiple sclerosis journal, 2018)
BACKGROUND: Serum immunoglobulin G targeting the astrocyte water channel aquaporin-4 (AQP4) in the central nervous system (CNS) is a biomarker for neuromyelitis optica spectrum disease (NMOSD). Co-existence of NMOSD with systemic lupus erythematosus (SLE) putatively suggests susceptibility to antibody-mediated autoimmune disease. OBJECTIVE: To estimate the prevalence of NMOSD in SLE and investigate the immunogenetic background for an association of NMOSD and SLE. METHODS: The study included a predominantly population-based cohort with clinical and serological investigations of 208 patients with SLE, followed prospectively since 1995. All patients received immunosuppressive treatment. NMOSD was evaluated retrospectively based on the 2015 International Panel for NMOSD Diagnosis (IPND) criteria. Polymorphisms in programmed cell death protein 1 (PDCD-1) PD-1.3 G/A were genotyped. AGP4-IgG and other autoantibodies, including myelin oligodendrocyte glycoprotein (MOG), was determined blinded to clinical diagnosis. RESULTS: Of 208 patients with SLE, 45(22%) had neuropsychiatric (NP) SLE, and CNS involvement predominated in 30 of 45 (67%) patients. Serum AQP4-IgG was detected in 2 of 30 (6.7%) neuropsychiatric SLE (NPSLE) patients both of whom had myelitis and antiphospholipid syndrome; one patient also had myasthenia gravis. None had MOG-IgG. PD-1.3A allele was not associated with SLE nor with NPSLE. CONCLUSION: AQP4-IgG autoimmune syndrome may rarely co-exist with SLE, and such patients have other NMOSD-typical syndromes such as myelitis.